Identity, Ethnicity, and Religious Changes in Bihor County, Romania. Reflections on the Changes of Romanian and Hungarian Christian Denominations in Bihor County during the 20ᵗʰ Century. The Case of Érselénd/Șilindru - KOVÁCS, Ábrahám; SZILÁGYI, Ferenc (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
The purpose of the research is to offer a three-dimensional examination of a chosen population’s make-up, examining ethnicity, native language, and religious denomination during the 20th century in the Romanian Bihor County. This pa-per examines the changing process of how identity in Érselénd/Șilindru was influenced by outside forces coming from different social, political, religious, and even economic directions. The village was chosen, as it was originally a Ruthenian-speaking Greek Catholic settlement that moved to the Hungarian Kingdom centuries ago. They kept their religious identity but became Hungarian-speaking people. Then, during the twentieth century, this homogenous settlement, due to external political, historical, and economic influences, experienced a profound change to a degree that had not been predicted. However, this frag-mentation into various Christian denominations, the changes of language and ethnic identity clearly demonstrates the complex history of the geopolitical region of Partium, Romania.